Dual-band transparency over near-IR and THz in surfactant-free DNA solid film - Jeong, Hayoung; Cheona, Seunguk; Lee, Yong Soo; Ghasemi, Marjan; Kim, Soeun; Kang, Chul; Maeng, Inhee; Hong, Seongjin; Oh, Kyunghwan (Nature Publishing Group, 2024)
We thoroughly investigated the optical properties of surfactant-free deoxyribonucleic acid (SF-DNA) solid films across a broad spectral gamut from ultraviolet (UV) to terahertz (THz). Demonstrating potential as a transparent dielectric material, SF-DNA films could potentially form optical elements, such as lenses, prisms, and waveguides, for dual-band, near-IR and THz applications. SF-DNA films were classified according to their thickness. Nanometer scale films, ranging from 40 to 200 nm, were created by employing spin coating techniques with aqueous DNA solutions on silicon or fused silica substrates. Micrometer scale films, ranging from 1 to 300 mu m, were formed as freestanding DNA films using drop-casting methods. Additionally, we have achieved the successful fabrication of an SF-DNA solid cylinder, positioned between two optical fiber ends, featuring a diameter of 100 to 110 mu m and an axial length of 65 to 200 mu m. SF-DNA films exhibited a unique dual-band transparency in the near-IR spectral range of 1260 to 1870 nm, and in the terahertz range of 0.22 to 0.64 THz. The refractive index dispersion of nanometer-scale films and their birefringence were also measured in the range of 400 to 2,600 nm. The systematic analysis of optical characteristics from UV to THz wavelengths will serve as a critical foundation for further applications of SF-DNA films in the photonic and optoelectronic device fields.